Left behind: intergenerational transmission of human capital in the midst of HIV/AIDS - Mevlude Akbulut-Yuksel; Belgi Turan (Institute for the Study of Labor (IZA), 2010)
This paper provides evidence on how adverse health conditions affect the transfer of human capital from one generation to the next. We explore the differential exposure to HIV/AIDS epidemic in sub-Saharan Africa as a substantial health shock to both household and community environment. We utilize the recent rounds of the Demographic and Health Surveys (DHS) for 11 countries in sub-Saharan Africa that provide information on mother's HIV status and enable us to link mothers and their children. The data also allow us to distinguish between two separate channels that are likely to differentially affect the intergenerational transfers: mother's HIV status and community HIV prevalence. First, we find that mothers transfer 37% of their human capital to their children in the developing economies in sub-Saharan Africa. Second, our results show that mother's HIV status has large detrimental effect on inheritability of human capital. HIV-infected mothers are 30% less likely to transfer their human capital to their children. Finally, focusing only on non-infected mothers and their children, we find that HIV prevalence in the community also significantly impairs the intergenerational human capital transfers even if mother is HIV negative. The findings of this paper is particularly distressing for these already poor, HIV-torn countries as in the future they will have even lower overall level of human capital due to the epidemic.
Keywords: O12; I1; I2; 330; HIV/AIDS; intergenerational transmission; human capital investment